2018
DOI: 10.1136/esmoopen-2018-000320
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin dose based on actual renal function: no excess of acute haematotoxicity in adjuvant treatment in seminoma stage I

Abstract: IntroductionThe practice of carboplatin dosing is not concordant among different centres and oncologists. Some clinical guidelines recommend capping of the carboplatin dose at, for example, creatinine-clearance (Crea-Cl) of 125 mL/min because of concerns of excessive toxicity. Clinical data to support such recommendations are lacking, especially in patients with seminoma.MethodsThis is a retrospective analysis of acute haematotoxicity of patients with stage I seminoma treated with adjuvant carboplatin area und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…The value from the Cockcroft-Gault formula is then imputed into the Calvert equation, which is derived in 31 mostly female patients with an R 2 of 0.76 to calculate a carboplatin dose [41]. The calculated dose may be capped by the truncation of the glomerular filtration rate value at 125 mL/min [42], which is incorrectly assumed to be the physiological maximum [43].…”
Section: Discussionmentioning
confidence: 99%
“…The value from the Cockcroft-Gault formula is then imputed into the Calvert equation, which is derived in 31 mostly female patients with an R 2 of 0.76 to calculate a carboplatin dose [41]. The calculated dose may be capped by the truncation of the glomerular filtration rate value at 125 mL/min [42], which is incorrectly assumed to be the physiological maximum [43].…”
Section: Discussionmentioning
confidence: 99%
“…The value for creatinine clearance is then imputed into the Calvert equation, which is also biased, having been derived in only 31 mostly female patients with an R 2 of 0.76 [3]. The calculated dose may be capped by the truncation of GFR at 125 mL/min [12] (incorrectly assumed to be the physiological maximum [13]), or setting a lower limit value for SCr. It is therefore not a surprise that we do not accurately and precisely achieve the target AUC.…”
Section: Introductionmentioning
confidence: 99%
“…However, nephrotoxicity can be considered the result of oxaliplatin in cases of repeated exposure[ 52 ]. Carboplatin is known for its low nephrotoxicity, but only case reports have confirmed that carboplatin can cause biopsy-proven AIN[ 51 , 53 , 54 ].…”
Section: Mechanisms Of Aki In Patients With Gastrointestinal Tumorsmentioning
confidence: 99%